2017
DOI: 10.3389/fbuil.2017.00072
|View full text |Cite
|
Sign up to set email alerts
|

Toward Better Understanding of Turbulence Effects on Bridge Aerodynamics

Abstract: With the trend of variable cross-sections for long-span bridges from truss-stiffened to quasi-streamlined, and then to multiple-box cross-section geometries, the importance of aeroelastic performance is becoming increasingly significant in wind-resistant design. This article shows that there is clearly insufficient qualitative as well as quantitative understanding of turbulence effects on bridge aerodynamics, particularly the mechanisms behind them. Although turbulence might help the stabilization of long-span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…circular) and bridge-deck cross section, and the considerably less number of studies on the latter than those on the former. Cao et al (2017) reviewed a number of cases for the circular cylinder. They suggested that turbulence has a very strong influence on the extension of the lock-in region, and in some cases, turbulence can completely suppress the structure's response.…”
Section: Freestream Turbulence Effects On the Amplitude Of Viv Responsementioning
confidence: 99%
“…circular) and bridge-deck cross section, and the considerably less number of studies on the latter than those on the former. Cao et al (2017) reviewed a number of cases for the circular cylinder. They suggested that turbulence has a very strong influence on the extension of the lock-in region, and in some cases, turbulence can completely suppress the structure's response.…”
Section: Freestream Turbulence Effects On the Amplitude Of Viv Responsementioning
confidence: 99%
“…Anyways, the answer shall not necessarily be dichotomic; at least, the influence of turbulence should depend on the type of turbulence (its frequency content) and its intensity. In some studies, turbulence is shown to have a strong effect on the synchronization mechanism and may lead to a complete suppression of VIV (Cao and Cao, 2017). Other works tend to indicate that the grid turbulence of the oncoming flow has virtually no influence on the response amplitude (Goswami et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cao, S. and Cao, J. [5] briefly introduced a newly developed multiple-fan wind tunnel which is designed to control turbulence to assist the study of turbulence effects. Wang, J.Y, Meng, Q. H., Luo, B. and Zeng, M. [6] presented a new type of active controlled multiple-fan wind tunnel.…”
Section: Introductionmentioning
confidence: 99%